Mobility: exploratory analysis for territorial preferences - Santos, Alessandra G.T.; Moura, Ana Clara Mourão (TeMA - Journal of Land Use, Mobility and Environment, 2019)
Urban mobility is a current challenge on modern life and has its implications not only on time misuse but also on citizens’ health. Spending hours of a day on traffic, people interact with the environment they are susceptible to, which implicates on their manner of seeing, enjoying and living a city. To analyze this impact, an exploratory study was developed on the possibilities of using data composition and spatial analysis tools to select and combine main variables in order to diagnose characteristics of urban landscape on Pampulha Region, in Belo Horizonte (MG), Brazil. Territorial Analysis Units (UTA) were delimited and urban data were studied. First, the main characteristics were represented in categories of variables, and then they were recombined by utilizing Multi-Criteria Methods based on Weighted Sum to present results of suitability for walkability. For each step of spatial analysis, were generated Suitability (Multi-Criteria) and Sensitivity (Uncertainties) Evaluation Maps, proving the similarities of areas considered attractive and vulnerable with the goal to refine the partial results and select the main variables related to walkability. The case study presents the most significant characteristics that might be considered when planning quality of life on urban environments.